Perceived social support and deviant behavior of new street corner youth on campus: a moderated mediation model - Chi, Hong; Fan, Linlin; Meng, Weijie (Frontiers in Psychology, 2024)
Introduction The current study aimed to examine the moderated mediation between perceived social support, the deviant behavior of new street corner youth on campus (NSCYC), interpersonal needs (as a mediator), and meaning in life (as a moderator). Methods A total of 596 new street corner youth on campus were investigated using the Deviant Behavior Questionnaire, Perceived Social Support Scale, Interpersonal Needs Questionnaire, and Meaning in Life Questionnaire. Results The findings showed that: (1) perceived social support significantly and negatively predicted deviant behavior; (2) interpersonal needs mediated the association between perceived social support and deviant behavior; and (3) a moderated mediating role of perceived social support influencing deviant behavior was established, with meaning in life regulating both the direct and the first half paths of the model. Discussion These findings offer important insights into the factors influencing the deviant behavior of NSCYC. They highlight the role of perceived social support, interpersonal needs, and meaning in life, and suggesting intervention points to mitigate deviant behaviors of NSCYC.